Ateliers monétaires et mines d’argent dans les Alpes (xe-xve siècles). Histoire, archéologie, numismatique et archéométrie - Marie-Christine Bailly-Maître; Michel Dhénin (Archéologie Médiévale)
The production of silver is a technical and economical concern, but it is also political. From the 7th century until the reign of Philip IV the Fair, single metals are the rule for coins in France, silver being the most common. Stocks of ancient metal being insufficient, there consequently ensued a systematic search for sources of ore. The stakes put on what would now be considered as but very modest deposits express the determination of the ruling classes to control ore extraction and metal production. The project at the centre of our current reflections is to endeavour to establish a connexion between the production of this white metal, the activity of monetary workshops, and the power role in the opening of certain mines to provide ore for specific workshops, in the context of occasional or permanent political realities. For this, the historian has recourse to archives, the archaeologist to numismatics, and finally to analyses.